ANALISIS PRODUKTIFITAS INVESTASI SUMBER DAYA MANUSIA MELALUI SARANA PENDIDIKAN DAN PELATIHAN DI KOTA JAMBI - Bahri, Zainul (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2012)
This research is aimed to analyze the human resources investment (capital investment) in Jambi town; to see the investment description of cost magnitude has expenditure by human resources from various education level; to see the result of investment description is income magnitude that will receive human resources from various education level; analyze study of find out of rate of productivity the human resources investment that has increase the quality of human capital. The data used is primer data year of 2006 consist of cost & income data. Cost data take from itself students expenditure (begin kind garden school thru university student level) and Government Expenditure such are: operational cost student, scholarship, etc. Income data take from staff both are government employee or company employee and others data concerning to this research. Before analysis, the data will be construction by used Life Time Matrix method. The result of quantitative analysis shown that the magnitude productivity of human resources in produce labor productivity could see by the total productivity of human resources is 3, 0950. And as partial the measurement of productivity could calculate that the company employee has productivity rate is 4,9924 and the government employee has productivity rate is 3, 6734. It’s mean the rate of productivity of company employee higher than government employee (4,9924 > 3,6734).